2011
DOI: 10.1007/s00345-011-0744-6
|View full text |Cite
|
Sign up to set email alerts
|

When is it necessary to perform nuclear renogram in patients with a unilateral neonatal hydronephrosis?

Abstract: When the AP pelvic diameter is less than 20 mm at presentation, DRF is normal. If the AP diameter is stable or decreases, there is unlikely to be a significant deterioration in renal function. Consequently, in selected patients, congenital unilateral hydronephrosis can be followed with serial ultrasounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…They predicted that the mean APD in resolved cases was \10 mm [1]. Burgu et al suggested that DRF is preserved (C40 %) when APD is \20 mm [15]. Our results were also concordant with the results of these studies.…”
Section: Resultssupporting
confidence: 95%
“…They predicted that the mean APD in resolved cases was \10 mm [1]. Burgu et al suggested that DRF is preserved (C40 %) when APD is \20 mm [15]. Our results were also concordant with the results of these studies.…”
Section: Resultssupporting
confidence: 95%
“…4244 In addition, individuals with VACTERL association frequently have GU anomalies. 45 Physical examination may yield findings warranting further medical/surgical interventions.…”
Section: Suggested Diagnostic Approachmentioning
confidence: 99%
“…Only a few studies showed that giant hydronephrosis could be asymptomatic until the late stage (17), or only manifests with non-specific symptoms (18), such as fatigue or indigestion. The incidence of asymptomatic hydronephrosis among newborns is 0.5% to 1% (19), and the incidence of central DI is 3-4 patients per 100,000 (20). As asymptomatic hydronephrosis is more common, we should pay special attention to it when it is accompanied by DI, other nephrologic disorders or symptoms (increased water intake, strenuous exercise or urinary retention).…”
Section: Discussionmentioning
confidence: 99%